Von Willebrand disease type Vicenza: In search of a classification for the archetype of reduced von Willebrand factor survival. Issue 3 (5th May 2021) - Casonato, Alessandra; Galletta, Eva; Galvanin, Federico; Daidone, Viviana
Abstract: Type Vicenza von Willebrand disease (VWD) features a von Willebrand factor (VWF) with a very short half‐life, and is classified as a form of type 1 VWD. To test the appropriateness of type Vicenza VWD classification, the main features of 17 patients from eight unrelated families were analysed. They had low VWF antigen levels and function (always below 20 U/dl); ristocetin‐induced platelet aggregation sometimes normal, sometimes reduced/absent (even in the same patient); normal platelet VWF levels; an increased VWF propeptide to VWF antigen ratio (8.74 ± 1.65 vs. normal 1.04 ± 0.28) and a reduced VWF half‐life. Plasma VWF multimer levels were homogeneously reduced, and unusually large VWF multimers were sometimes present. Recombinant p.R1205H VWF showed a normal synthesis, release, function, and multimer pattern, with no ultra‐large VWF multimers. The mathematical model by Galvanin et al. was used to explore the kinetic changes in VWF after DDAVP. It showed that the release, but especially the proteolysis ( k proteol 1.0 −3 ± 2.5 −3 vs. normal 4.5 −4 ± 6.4 −4 ) and elimination ( k el 1.0 −2 ± 5.2 −3 vs. normal 1.1 −3 ± 6.8 −4 ) of type Vicenza VWF were significantly higher than normal. The increased elimination is consistent with the short half‐life, while the increased proteolysis was unexpected. As a shorter survival of VWF is wholly responsible for the type Vicenza VWD phenotype (VWF synthesis, structure and function are normal), it might be better to classify it as a type 2 VWD (rather than type 1) to emphasise the greater interaction with clearance receptors as a new VWF functional defect.